Hubungan Pemberian Asi Eksklusif dengan Peningkatan Berat Badan (BB) Bayi di Wilayah Puskesmas Penerokan Tahun 2025 - Hermatati Hermatati; Hasvia Berliani; Rosa Riya; Reni Hariyanti (Jurnal Akademika Baiturrahim Jambi, 2026)
The Relationship Between Exclusive Breastfeeding and Infant Weight Gain in Infant weight is an important indicator in assessing infant growth and nutritional status. Exclusive breastfeeding is one of the factors that contributes to infant weight gain. However, the coverage of exclusive breastfeeding in Indonesia has not yet reached the expected target. The purpose of this study was to determine the relationship between exclusive breastfeeding and infant weight gain in infants aged 0–6 months in the Penerokan Community Health Center working area in 2025. This research is quantitative analytical with a cross-sectional design. The population in this study was all mothers with infants aged 0–6 months in the Penerokan Community Health Center's work area, totaling 50 people, who also served as the sample using the total sampling technique. The results showed that of the 50 respondents, 31 mothers (62.0%) provided exclusive breastfeeding and 29 infants (58.0%) experienced appropriate weight gain. The analysis using the Chi-Square test obtained a P-Value of 0.000, which means there is a significant relationship between exclusive breastfeeding and infant weight gain. There is a link between exclusive breastfeeding and increased infant weight gain. Therefore, it is hoped that health workers will increase education and counseling regarding the importance of exclusive breastfeeding for breastfeeding mothers and their families.